Origin of Hot Bubble in NGC 6822 Hubble V Star-Forming Region. Issue Volume 14:Issue S344(2019) (August 2018) - Lee, Hye-In; Oh, Heeyoung; Lim, Beomdu; Le, Huynh Anh N.; Lee, Sungho; Mace, Gregory; Jaffe, Daniel T.; Tatematsu, Ken'ichi; Park, Sangwook; Pak, Soojong
Abstract: We observed a bright H II complex, Hubble V in NGC 6822, using the high-resolution near-infrared spectrograph IGRINS (R = 45, 000) attached on the 2.7 m telescope at the McDonald Observatory. We carried out a spectral mapping over a 15″ × 18″ region in the H and K bands using a slit-scanning technique. The emission lines Brγ and He i from ionized regions as well as molecular hydrogen lines from photo-dissociation regions (PDRs), were detected. We show three-dimensional maps of the emission lines and discuss the possibility of an expanding hot bubble structure within which many ionized components are around the central stellar cluster.